Research into the thermal stability and mechanical properties of vitamin E diffusion modified irradiation cross-linked graphene oxide/ultra-high molecular weight polyethylene composites. Issue 8 (24th January 2020) - Duan, Weipeng; Wu, Meiping; Han, Jitai; Ni, Zifeng
Abstract : Recently, there has been increasing interest in modifying ultra-high molecular weight polyethylene (UHMWPE) due to glaring needs in the artificial joint replacement field. Abstract : Recently, there has been increasing interest in modifying ultra-high molecular weight polyethylene (UHMWPE) due to glaring needs in the artificial joint replacement field. It is generally reported in the literature that irradiation cross-linking and adding graphene oxide (GO)/vitamin E (VE) can enhance the mechanical properties of UHMWPE, but this can sacrifice the oxidation stability and gel content. This paper examines how VE diffusion can influence irradiation cross-linked GO/UHMWPE composites and whether mechanical performance and oxidation resistance can be maintained simultaneously, which will provide new guidance for prolonging the longevity of UHMWPE implants. The GO/UHMWPE composites were fabricated by means of liquid ultrasonic dispersion, hot pressing and irradiation cross-linking, followed by VE diffusion and homogenization treatment. The results indicated that limited VE diffusion decreased the water absorption and wettability. The crystallinity, melting temperature, thermal stability, hardness and scratch resistance of the composites basically remain essentially the same, except in the case of pure UHMWPE. In addition, the oxidation resistance was improved significantly after incorporating VE. Furthermore, the diffusion and enhancement mechanisms were also demonstrated, respectively.